King’s Landing vs. Dubrovnik – The study of image and identity management in a film tourism destination - Töniste,Raili (2018)
In today’s world, where viewing television is one of the most prominent leisure activities, it is only natural that the scenes seen on the screen can have an impact on the image that people have of certain destinations. While film tourism is not a new phenomenon, it is relatively young in academic research and many aspects and perspectives are yet to be examined. This paper makes use of the stakeholder theory to examine place identity and destination image management in Dubrovnik, Croatia in relation to Game of Thrones tourism. Making use of qualitative semi-structured interviews and content analysis, the study revealed that Dubrovnik, a city with a strong existing identity discourse does not face a threat to its identity from Game of Thrones or any other production filmed in the city. While the show has created a lot of publicity and exposure to the city, the film tourism stakeholders consider the show as a trend that will pass with time, however are meanwhile happy to make use of the show as an additional activity and a unique selling point to offer to visitors.
Keywords: place identity; destination image; film tourism; Game of Thrones tourism; Dubrovnik; stakeholder theory